Planning and Management of Urban Green Spaces in Europe: Comparative Analysis - Baycan, T.; Nijkamp, P. (American Society of Civil Engineers (ASCE), 2009)
The present paper analyzes and compares the current urban green space planning and management experiences of 23 European cities in order to understand the critical factors behind their success and/or failure and to obtain strategic and policy relevant information on the key features of urban green provisions and maintenance. The results of our comparative analysis show that - despite a variety in urban green space policies in cities in Europe - the critical success conditions in planning and management of urban green spaces have emerged in four factors/attributes: (1) the share of green space in urban land use; (2) the changes in these shares over time; (3) the intensity of involvement of the city administration; and (4) the degree of citizen participation. The comparative evaluation of our analysis also shows some interesting results in terms of geographical and regional characteristics in the success level. We can say that three geographical regions, northern Europe, southern Europe, and eastern Europe, with different success levels and characteristics, have emerged in the green picture of Europe. © 2009 ASCE.